2014
DOI: 10.1371/journal.pone.0102776
|View full text |Cite
|
Sign up to set email alerts
|

Light Exposure at Night Disrupts Host/Cancer Circadian Regulatory Dynamics: Impact on the Warburg Effect, Lipid Signaling and Tumor Growth Prevention

Abstract: The central circadian clock within the suprachiasmatic nucleus (SCN) plays an important role in temporally organizing and coordinating many of the processes governing cancer cell proliferation and tumor growth in synchrony with the daily light/dark cycle which may contribute to endogenous cancer prevention. Bioenergetic substrates and molecular intermediates required for building tumor biomass each day are derived from both aerobic glycolysis (Warburg effect) and lipid metabolism. Using tissue-isolated human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 37 publications
7
124
0
1
Order By: Relevance
“…Work by Santoro et al (2013) demonstrated that blockade of MT 1 /MT 2 receptors in MCF-7 cells impairs p53-mediated prevention of DNA damage. Other mechanisms associated with the anti-proliferative actions of melatonin include cell cycle with arrest of breast tumor cells in the G1 phase of the cell cycle (Cos et al 1991), repression of estrogen synthesis in the gonads (Blask et al 2011) or the tumor by repression of aromatase (Martínez-Campa et al 2009), and finally by suppression of tumor metabolism (Warburg effect) via repression of tumor uptake of free fatty acids, particularly linoleic acid and its conversion to 13-hydroxyoctadecadienoic acid (13-HODE) (Reiter 1991; Blask et al 2014). …”
Section: Anti-proliferative Actions Of Melatonin In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Santoro et al (2013) demonstrated that blockade of MT 1 /MT 2 receptors in MCF-7 cells impairs p53-mediated prevention of DNA damage. Other mechanisms associated with the anti-proliferative actions of melatonin include cell cycle with arrest of breast tumor cells in the G1 phase of the cell cycle (Cos et al 1991), repression of estrogen synthesis in the gonads (Blask et al 2011) or the tumor by repression of aromatase (Martínez-Campa et al 2009), and finally by suppression of tumor metabolism (Warburg effect) via repression of tumor uptake of free fatty acids, particularly linoleic acid and its conversion to 13-hydroxyoctadecadienoic acid (13-HODE) (Reiter 1991; Blask et al 2014). …”
Section: Anti-proliferative Actions Of Melatonin In Breast Cancermentioning
confidence: 99%
“…For example, in human breast cancer xenografts grown in athymic female nude rats, greatly elevated tumor uptake of LA and metabolism to 13-HODE and aerobic glycolysis during the daytime are involved in promoting a corresponding increase in cell proliferative/survival activities in tumors, whereas during the nighttime, these processes become quiescent as shown by much lower cell proliferative rates and increased cell loss. Therefore, the relatively slow net tumor growth rate in the presence of an intact nocturnal circadian melatonin signal reflects an overall balance in tumor circadian dynamics characterized by a up-regulation of daytime metabolism, signaling, proliferation and cell survival offset by a highly significant down-regulation of these activities during the nighttime (Blask et al 2014). …”
Section: Melatonin Effects On Tumor Metabolic Activitymentioning
confidence: 99%
“…hemostasis [58], the ribosome biogenesis suppression [59], inhibition of cAMP formation, induction of p53, and p21 upregulation. Additionally it seems that the suppression of linoleic acid uptake and its conversion to 13-hydroxyoctadexadienoic acid (13-HODE), associated with the reduction of breast cancer cells metabolism through melatonin treatment may boost the melatonin anti proliferative effects [12,29,60].…”
Section: Melatonin Suppresses Cell Proliferation In Breast Cancermentioning
confidence: 99%
“…Therefore, some antitumor effects of melatonin correlate with melatonin receptor (MT 1 / MT 2 )-dependent inhibition of linoleic acid uptake [89]. In addition, melatonin could suppress the Warburg effect by reducing 13-HODE formation and thus activation of AKT, which is a major stimulatory pathway for aerobic glycolysis [92]. …”
Section: Inhibition Of Linoleic Acid Uptakementioning
confidence: 99%